Méndez, Ricardo (2018). La telaraña financiera: Una geografía de la financiarización y su crisis - Gutiérrez Hernández, Oliver (Documents d’Anàlisi Geogràfica, 2020)
Méndez, Ricardo (2018) La telaraña financiera: Una geografía de la financiarización y su crisis Barcelona: RiL Editores, 424 p. ISBN 978-956-01-0582-0